Dakwah Syekh Jangkung Di Palembang: Analisis Komparatif Sumber Sejarah Lokal Dan Jawa - Solimin; Qomarullah, Muhammad; Muklis (STAI Bumi Silampari, 2025)
This study analyzes the traces of the da'wah of Sheikh Jangkung (Sayyid Raden Syarifuddin) in Palembang by comparing the Javanese hagiography narrative and the local historical context. The background of this research departs from the